Impact of Laparoscopic Sleeve Gastrectomy on Gut Permeability in Morbidly Obese Subjects - Kellerer, Teresa; Brandl, Beate; Büttner, Janine; Lagkouvardos, Ilias; Hauner, Hans; Skurk, Thomas (Obesity surgery, 2019)
Background Recent studies have suggested that obesity is associated with an increased intestinal permeability as well as an altered microbiota profile. These conditions can promote the translocation of lipopolysaccharide into the circulation and, subsequently, contribute to the observed systemic inflammation. Our aim was to assess gut permeability in patients with obesity compared to non-obese subjects as well as after excessive weight loss following laparoscopic sleeve gastrectomy (LSG). Methods We analyzed the dietary intake, metabolic and inflammatory markers, gut permeability (four-probe sugar test), and microbiota composition in 17 morbidly obese patients before and after LSG as well as in 17 age- and gender-matched non-obese subjects. Additionally, we compared gut permeability and inflammatory markers in patients of different stages of obesity. Results Patients with obesity showed elevated levels of C-reactive protein and lipopolysaccharide-binding protein as compared to non-obese subjects, but no differences were noted for gut permeability between these two groups. LSG led to improvements in metabolic and inflammatory parameters in the obese patients. Moreover, gastroduodenal as well as small intestinal permeability decreased, whereas colonic permeability increased after surgery. Regarding gut microbiota, differences were noted for main phyla and alpha-diversity between non-obese and obese subjects. After surgery, the composition of the microbiota showed a tendency toward the pattern of the non-obese group. Conclusions Gut permeability is not dependent on body mass index, whereas weight loss after LSG initiates distinct changes in gastroduodenal, intestinal, and colonic permeability. These changes do not seem to be associated with changes in the microbiota composition. Clinical Trial Registry Number and Website The trials were registered at https://www.drks.de/drks_web/ with the number DRKS00009008 and DRKS00006210.